Leptospira Gene analysis - Erkihun Aklilu; Kalthum Hashim; Abd Rahman Aziz (2013)
Leptospirosi is emerging as global importance widespread zoonosis that affects both humans and animal. It is caused by members of spirochetes belonging to the genus Leptospira. The transmission of leptospirosis occurs primarily through urine of infected animals and urine contaminated water or soil. early diagnosis of leptospirosis ie essential since antibiotic theraphy provides greatest value when administered early in the course of illness. Unfortunately,leptospirosis is often diagnosed late due to non-specific clinical manifestations ranging from a flu-like syndrome to renal failure. An extensive understanding of the gene available in GenBank is crucial to design a convenient molecular detection using bioinformatics gene analysis. There are gene dependants in Leptospira species and or serogroup dependent. Most of the genes are species dependent and certain are serogroup dependant. This study was to identify Leptospira genes vailable in GenBank that correspond to pathogenic Leptospira species. Ten genes were analyzed by using multisequences alignment (BioEdit) and phylogentic tree (MEGA 5.2) which is 16S rRNA. LipL32, LipL41.SeeY,LigA,LigB,LigC,FlatB, GyrB and O-antigen polymerase.Aix out of ten genes were identified as species dependants which are 16S rRNA, Lip32,LipL41, SecY,FlaB and GyrB. O-antigen polymerase was identified as serogroup dependent.This study was able to identify gene that correspond to species dependant and can be used for designing convenient molecular detection and differentiation on pathogenic leptospira species.